2023
DOI: 10.2147/prbm.s406942
|View full text |Cite
|
Sign up to set email alerts
|

Primary Healthcare Pharmacists’ Perceived Organizational Support and Turnover Intention: Do Gender Differences Exist?

Abstract: Purpose This study aims to explore the relationship between the four-dimensional structured perceived organizational support (emotional support, instrumental support, supervisor support, and coworker support) and the turnover intention of pharmacists in primary healthcare institutions. The gender differences between perceived organizational support and turnover intention will also be examined. Methods A cross-sectional study was conducted in primary healthcare instituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…, 2021; Henrique and Godinho Filho, 2020). Furthermore, in both public and private healthcare facilities, different behaviours may emerge by virtue of different and pluralistic gender orientations (Li et al. , 2023) and impact the quality of hospital outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2021; Henrique and Godinho Filho, 2020). Furthermore, in both public and private healthcare facilities, different behaviours may emerge by virtue of different and pluralistic gender orientations (Li et al. , 2023) and impact the quality of hospital outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in most cases, the implementation of LSS is not unique and does not always move along expected trajectories, so the evaluation of implementation in different contexts, such as the public and private Italian ones, is of great importance (Rosa et al, 2021;Henrique and Godinho Filho, 2020). Furthermore, in both public and private healthcare facilities, different behaviours may emerge by virtue of different and pluralistic gender orientations (Li et al, 2023) and impact the quality of hospital outcomes. Evidence in the literature has shown that, differing from gender, a variable inclination for risk-taking and goal setting rises (Dafna, 2008), while the motivation to work (Moody and Pesut, 2006) in teams or exhibit emotional intelligence (Deshpande and Joseph, 2009) may improve professionals' experience.…”
Section: Introductionmentioning
confidence: 99%